WIPO collection of leading judgments on intellectual property rights : members of the African Intellectual Property Organization (1997-2018) - Elongué, Max Lambert Ndéma; Fometeu, Joseph (World Intellectual Property Organization, 2023)
This casebook of selected judgments from the member states of the African Intellectual Property Organization (OAPI) is the second volume in the WIPO Collection of Leading Judgments on Intellectual Property Rights. This collection gives the global intellectual property (IP) community access to landmark judgments from jurisdictions that are among the most dynamic litigation venues or whose jurisprudence is not readily available to an international audience, through a succession of volumes that illustrate IP adjudication approaches and trends by jurisdiction or by theme.